The Bele Alis Sermon: Homiletic Song and Dance - Taylor, Robert A.; Pfeffer, Wendy; Rosenfeld, Randall A.; Weiss, Lys Ann [Shore] (Florilegium, 2007)
This article provides a study and edition of a unique text, a Latin sermon based on the text of a popular Old French dance-song. The attribution of the text in Mss. A and C to Stephen Langton, Archbishop of Canterbury, has been challenged but has not yet been convincingly disproved. Analysis of the sermon reveals a complex inner structure that interlinks the popular song with its Marian interpretation by a series of subtle echoes and suggestive images. The study of the sermon's architecture sheds new light on the intertextuality and interpretation of the concurrent voices in polytextual motets. A new critical edition of the text is furnished, utilizing all seven manuscripts, based on Ms. A, translated into English for the first time.